PENGARUH DESAIN PRODUK DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA HONDA SCOOPY PADA ASTRA MOTOR - Dita Asriani; Muhajirin Muhajirin (Program Magister Manajemen Indo Global Mandiri University, 2021)
Satisfying consumer needs is the dream of every company. Apart from being an important factor for the company's survival, meeting consumer needs can increase its superiority in competition. Consumers who are satisfied with product design and product quality tend to buy back the product and reuse the product when the same need arises at a later date. This study aims to determine the effect of product design and product quality on consumer satisfaction at Honda Scoopy on Astra Motor. This study uses a quantitative approach with a survey method, while this type of research includes associative research. The population in this study are consumers who have used Honda Scoopy, the number of samples taken in this study were 100 respondents. The sample used in this study was purposive sampling. The research instrument used a questionnaire with a Likert scale. Data analysis used multiple linear regression, correlation test, determination test, partial test analysis with t test and f test (simultaneous). To test the effect between variables using SPSS (Statistical Service Product Solutions) version 23.00. The results based on the t test (partial) show that product design affects customer satisfaction, product quality affects product satisfaction, while product design and product quality simultaneously affect product satisfaction.